Radon on Mars and the Moon derived from Martian and lunar meteorites - Frédéric Girault; Ludovic Ferrière; Carine Sadaka; Íñigo de Loyola Chacartegui Rojo; Rémi Losno; Frédéric Moynier; Frédéric Perrier; Pierre-Yves Meslin (Scientific Reports)
Abstract The radioactive gas radon-222, a fluid and aerosol tracer in Earth’s lithosphere and atmosphere, can also reveal subtle rock physics processes in extraterrestrial environments, such as those involving water, but remains poorly constrained in planetary bodies due to the limited number of samples available. Here we measure the effective radium-226 concentration (EC Ra) of six Martian and nine lunar meteorites to derive radon source terms for Martian and lunar rocks. EC Ra values are 0.029–0.78 and 0.045–0.80 Bq kg−1 for Martian and lunar meteorites, respectively (0.041 ± 0.003 Bq kg−1 for falls and 0.28 ± 0.02 Bq kg−1 for finds), lower than most terrestrial rocks but similar to other meteorites and terrestrial primitive basalts. The effect of terrestrial alteration on EC Ra and its temperature sensitivity are also determined experimentally. Radon emanation coefficient values are 2.1–17% (mean: 8.1 ± 2.5%) for Martian meteorites and 0.43–11% (mean: 5.5 ± 1.0%) for lunar meteorites. Mean estimated surface radon fluxes for Mars and the Moon are 0.16–0.60 and 0.33–0.44 mBq m−2 s−1 (78–280 and 160–210 atoms m−2 s−1), respectively, much lower than on Earth (21 mBq m−2 s−1 or 104 atoms m−2 s−1). Our meteorite analyses constrain radon emanation on Mars and the Moon and provide a basis for current and future in-situ measurements.